Descriptions of Adolescent Holistic Knowledge About HIV/AIDS at State Islamic Junior High School 2 Jember - Rosidah, Chilmiyatur (citeus, 2024)
HIV/AIDS is a global health issue, with the number of sufferers tending to increase each year. In 2015, there were 30,935 new HIV cases, and by 2020, this number had risen to 41,987 cases, indicating a 35.77 percent increase in new cases between 2015 and 2020. Adolescents constitute one of the groups vulnerable to HIV/AIDS due to a lack of holistic knowledge on the subject. Knowledge related to HIV/AIDS is crucial for adolescents, as the adolescent phase is characterized by an increase in hormone production, which may trigger risky sexual behavior. This study used a qualitative descriptive method with Focus Group Discussion (FGD) with 22 respondents at State Islamic Junior High School 2 Jember grades 7 and 8. The five indicators of knowledge asked respondents include definition, mode of transmission, characteristics of people affected, prevention and treatment of HIV/AIDS classified as less. Based on research results, knowledge about HIV/AIDS among adolescents is still relatively low, despite the respondents being organizational activists at school. As adolescents active in their organizations, they play an important role in disseminating appropriate information about HIV/AIDS to their peers. To address this issue, it is recommended that schools and other relevant stakeholders provide comprehensive sexual education for adolescents. Integrating education on sexual health into school subjects can help adolescents understand this disease comprehensively and realize the importance of sexual health and HIV/AIDS prevention.